A reflection on Attar Neyshabouri's Masnavi illustration - Ishan Agha, Eshrat (2021)
Image or imagination, ink and paste are the main themes of poetry, and since the end of the sixth century, which is one of the most fertile periods of Persian literature, the poets of this period freely imposed many poetic fantasies on Persian literature, And for centuries, with various acquisitions, they were influential in the poetry of the poets of the generations after them (Shafiee, 1999, pp. 404 and 405). The use of abstract and difficult philosophical and philosophical concepts in mystical poetic works has been common in various ways and forms in the form of allegorical anecdotes, educational stories and moral sermons. And provides various perspectives for the study and evaluation of such works. Attar Neyshabouri also believes that the world is a picture of the beauty of truth that reflects all the beauties of the beloved in itself, and one can easily see the attributes of beauty in the world and creatures. Since Attar Neyshabouri is both a poet, a Sufi and a sage, his works can be examined from three mystical, philosophical and literary perspectives. Attar Neyshabouri's works, such as his Masnavi, are among the mystical works in which the poet has used legal and philosophical themes and terms in accordance with the subject. He has also benefited greatly from the elements of imagery in order to make his words effective. In this discourse, the method of illustration and the method of using the elements of imagination, such as simile, metaphor, permission, irony, have been evaluated.